Coming Out (as a Poststructuralist): A Rant. (January 2019) - Teman, Eric D.; Lahman, Maria K. E.
The authors, within the context of the first author Eric's experiences, explore the politics of a hostile, academically violent pretenure environment as a poststructuralist scholar within a framework of cultural humility. Within this essay, we illuminate issues Eric experienced only after the idea of early tenure was presented by his dean. Most faculty were supportive of Eric and his research; a few were not. We examine issues of prejudice in scholarly works traditionally left unexplored. We wonder what is lost when one way of knowing is privileged over others and advocate for methodological humility. We question the depth of others' approaches to research when their philosophical stances are unclear and uninterrogated. We challenge researchers to understand and accommodate research approaches which differ from more "received" approaches. We challenge ourselves and qualitative colleagues to assist in the process of respecting and advocating for aesthetic qualitative representations by including them in comprehensive literature reviews. We encourage all scholars to be thoughtful, reflexive, and respectful with colleagues and themselves in their research pursuits.